Determinant Factors of Fintech Adoption in Organization using UTAUT Theory Approach - Florentina Kurniasari; Prio Utomo; So Yohannes Jimmy (Profesional Muda Cendekia Publishing, 2023)
The presence of Financial Technology (FinTech) as an innovative and disruptive financial service can improve the efficiency and scope of organization business process through the application of technology. In determining the effectiveness of Fintech adoption, each organization will measure by considering both from the perspectives of management and user in the organization. This proposed study aims to examine the effect of FinTech adoption in organization using the UTAUT approach. It attempts to measure the variable of performance expectancy, effort expectancy, social influence, customer’s trust and regulatory services into the effect of FinTech adoption in the organization. This study adopts quantitative method through online survey and the data will be analyzed by using Structural Equation Method (SEM). This proposed study’s findings could contribute by enhancing the organization the importance of FinTech adoption to increase business performances. The study showed that the the adoption of FinTech in organization had significantly influenced by performance expectancy, effort expectancy, social influence, customer trust as well as regulatory services. Customer trust itself had the highest influenced among others. Meanwhile, regulatory services had the smallest influence to the FinTech adoption in Organization.